Authority of Final Decision in Household Activities: Gender Perspective in Nepalese Society - Shrestha, Anita; Gartoulla, Ritu Prasad (Journal of Advanced Academic Research, 2018)
Gender plays the significant role in decision making process in all types of society. Decision makers should have good leadership skill as well as should have adequate knowledge of concerned issue. In Nepalese society, decision is taken by the household head; either husband or wife. The study aims to identify the authority of final decision in household activities from the gender perspective in Nepalese society. The study was conducted among the 390 respondents of five ethnic groups: Newar, Magar, Tamang, Rai and Brahama/Chettri of Kathmandu valley. Simple random sampling technique was adopted to select the respondent considering the equal participation of male and female from all ethnic communities. The result shows that there was no significant difference in all ethnic groups regarding their participation in all types of decision making process.